A combined use of TRIZ methodology and eco-compass tool as a sustainable innovation model - Boavida, Rodrigo (2020)
The authors acknowledge Fundacao para a Ciencia e a Tecnologia (FCT-MCTES) for its financial support via the project UIDB/00667/2020 (UNIDEMI).